ANALSIS KEMAMPUAN LITERASI SAINS SISWA KELAS V DI MIN 9 MEDAN - Wina Mariana; Titin Rahmayanti Rambe (Jurnal Sintaksis, 2021)
The purpose of this study is to be able to parse and find problems in scientific literacy activities through online media so that they can be improved and developed further and better in the future. . The research subjects were students of Class V SD MIN 9 Medan. The instrument used is a scientific literacy test tool developed by the author with reference to the indicators contained in the development of the TOSLS test. The data collection technique is by observing the activities of teachers and students and a questionnaire containing 20 questions concerning student learning activities. Results of Students' Science Literacy Ability Based on the TOSLS Indicator with Good Category there are 5 indicators, then with Enough Category there are 2 indicators and Poor Category there are 2 indicators. With a total of all categories included in the assessment of “PAIR”